-u/6=-42

Simple and best practice solution for -u/6=-42 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -u/6=-42 equation:


u in (-oo:+oo)

-u/6 = -42 // + 42

42-u/6 = 0

42-1/6*u = 0 // - 42

-1/6*u = -42 // : -1/6

u = -42/(-1/6)

u = 252

u = 252

See similar equations:

| 20=2+3u | | (7x^4)/(sqrt(2x-8)) | | 2.3log(x)=3log(6-x) | | 6x+y+z=10 | | -4u+5=5-4u | | 1920*x=5 | | -15=4u-3 | | 4lnx-1=6 | | 5/4=7x^2-x | | 42+x=(13+x)*2 | | 21y+7=5 | | 5/2*32 | | Y=-xy-3x-3 | | 11=2/3x-3 | | 2y=5y-8 | | 1920*x=2 | | x-(0.75x+1)=1 | | 4=4xW | | 4x^3+18x=0 | | 7-3-2/5v | | 3x-(x+1)=9 | | x+55=4x-5 | | 0=60+12.5x-4.9x^2 | | -16+3=-24+8x | | 3x*5y=1450 | | 15y+20x=525 | | 30+9k=3(4k+7) | | 42+x=(13+x).2 | | (b+6)(b+4b)= | | r^3+3y^2-4=0 | | -7+35=207x | | 19y+9=y-351 |

Equations solver categories